2016
DOI: 10.3945/ajcn.116.137711
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of short-chain fatty acids to the human large bowel

Abstract: The cecum and colon are an integral, but somewhat neglected, part of the human digestive system. This digestion is affected not by human enzymes but by the microbiota that degrade undigested dietary components and body secretions that pass through the ileocecal valve. The main fermentative substrates are the indigestible polysaccharides that constitute the greater part of total dietary fiber, whereas the short-chain fatty acids (SCFAs) 2 acetate, propionate, and butyrate are important end products (1). General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Dietary strategies to raise SCFAs in the large bowel, therefore, may be of public health and clinical benefit. For example, starch-butyrate ester and inulin-propionate ester were developed to increase the respective SCFA productions, aiming at colorectal cancer protection and appetite regulation in humans. …”
Section: Introductionmentioning
confidence: 99%
“…Dietary strategies to raise SCFAs in the large bowel, therefore, may be of public health and clinical benefit. For example, starch-butyrate ester and inulin-propionate ester were developed to increase the respective SCFA productions, aiming at colorectal cancer protection and appetite regulation in humans. …”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that their polysaccharides enhance feed efficiency of broilers (Khan et al, 2019). Although the effect on the intestinal microbiota was not evaluated in this study, other studies reported more efficient use of dietary nutrients and increased proliferation of epithelial cells at the intestinal level as the results of reduction in the intestinal pathogens, coupled with increased intestinal absorptive area (Topping, 1996;Józefiak et al, 2007), which promotes both feed digestibility and animal performance (Rehman et al, 2006;Rehman et al, 2007a,b).…”
Section: Discussionmentioning
confidence: 77%
“…In preliminary studies, it was demonstrated to improve metabolic homeostasis in diet-induced obese mice and caused bacterial shifts and increased fecal SCFAs during 3 week supplementation in humans [28,47,52,55]. Additionally, studies are beginning to examine the ability to transform insoluble fibers to more soluble ones to improve digestion [129] or to try and replace polysaccharide chains directly with SCFAs to site-deliver SCFAs to the colon instead of relying on bacterial fermentation [130]. Furthermore, newly composed synthetic fibers such as Gum Arabic, also known as Acacia Gum, have been shown to decrease BMI and adiposity in humans with type 2 diabetes [127], however more research is necessary to determine mechanistic differences with synthetic fibers.…”
Section: Discussionmentioning
confidence: 99%